Gangguan Berbahasa Tataran Fonologis pada Penderita Afasia Pasca Stroke Tipe Iskemik - Mukminati Zulfa; Jeny Marsela; Septriyadi Dafis Nur; Fatmawati Fatmawati (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to examine the language disorders that occur in post-stroke aphasia sufferers because this language disorder often occurs in society, but people are often not aware of the causes of this disease which makes people's communication in everyday life sometimes misinterpret or fail to understand aphasic sufferers who experience problems in producing speech. This study uses a descriptive approach. In researching literary works, formal qualitative research data is obtained from novel texts in the form of words, sentences, and discourse. The results of this study were cognitive-language impairment in patients with Broca's aphasia after a non-hemorrhagic stroke. The case study in AA experienced syllable deviations at the beginning, middle and back. Based on the research results obtained by the author, regarding language disorders at the phonological level found in AA patients with ischemic type post-stroke aphasia are (1) the omission of phonemes. The forms of errors that occur in the speech of AA patients with ischemic type post-stroke aphasia are: (1) omission of trill sounds, (2) omission of vowel sounds, (3) omission of more than one phoneme sound.